Multispectral snapshot demosaicing via non-convex matrix completion - Antonucci, G; Vary, S; Humphreys, D; Lamb, R; Piper, J; Tanner, J (IEEE, 2019)
Snapshot mosaic multispectral imagery acquires an under-sampled data cube by acquiring a single spectral measurement per spatial pixel. Sensors which acquire p frequencies, therefore, suffer from severe 1/p undersampling of the full data cube. We show that the missing entries can be accurately imputed using non-convex techniques from sparse approximation and matrix completion initialised with traditional demosaicing algorithms. In particular, we observe the peak signal-to-noise ratio can typically be improved by 2 dB to 5 dB over current state-of-the-art methods when simulating a p = 16 mosaic sensor measuring both high and low altitude urban and rural scenes as well as ground-based scenes.